Geomagnetic field effects on the performance of 8-inch dynode photomultiplier tubes - Fu, Zaiwei; Gao, Feng; Wang, Wenwen; Xia, Jingkai (Frontiers in Physics, 2023)
Two different systems have been built to study the geomagnetic field effect on the performance of large area photomultiplier tubes. The main characteristics of photomultiplier tubes such as gain, collection efficiency, transition time spread and energy resolution were measured to investigate the effect. This study shows that both the dynode structure and the orientation of photomultiplier tubes have a large influence on the performance due to the geomagnetic field effect. Different methods were proposed and tested to reduce these effects. The results were obtained with and without high-permeability permalloy foil shielding. It is found that the effect of the geomagnetic field can be significantly reduced by the permalloy foil. The influence of the geomagnetic field under different installation geometries is also studied and discussed in this paper.